Digitalna ekonomija - Ahtik, Meta (Podjetje in delo, 2017)
The objective of the article is to demonstrate the many dimensions of digital economy and its impact on future legal development. Digitalisation of economy is one of the economic megatrends in modern society, a process creating value by connecting products to Internet and producing spillover effects on this basis. Considering its multifaceted character, digitalisation of economy inherently touches upon the full spectrum of legal fields. The article first presents an overview of the legal challenges of the Internet of Things, pointing out several open issues related, in particular, but not exclusively to intellectual property, protection of personal data, privacy and consumer protection. It then considers Uber and the awaited decision of the Court of Justice of the European Union that will determine whether Uber is purely a transport company or an Internet platform. Legal consequences of each of the possible decisions differ significantly. Finally, it presents the challenges related to Bitcoin as the most representative virtual currency that is currently predominantly regulated only in the fields of taxation, prevention of money laundering and terrorist financing. It may be observed that the law promotes the positive aspects of digitalisation of economy, while simultaneously restraining its negative implications for the European economy and society.
Keywords: 3D printing; 3D-tiskanje; big data; bitcoin; cloud manufacturing; digital economy; digitalizacija industrije; digitalno gospodarstvo; digitising industry; ekonomija delitve; internet of things; internet stvari; oblak proizvodnje; servitisation; sharing economy; storitvizacija; veliko podatkovje